JUSTICE COLLABORATOR DALAM TINDAK PIDANA PEMBUNUHAN PERSPEKTIF MAQASID SYARIAH - Ismail Pane; Mara Ongku Hsb (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
Crimes such as murder and loss of a person's life are unlawful acts that are very contrary to humanity and justice in the Supreme Court circular letter number 4 of 2011 concerning justice collaborators (actors of witnesses who work together) will get legal remissions which are still limited to cases such as corruption, terrorism, narcotics, money laundering and human trafficking. The research method is a normative juridical descriptive method, namely the object of research related to the applicable laws and policies. The research results in the Supreme Court circular letter no. 4 of 2011 justice collaborators for the crime of murder are not clarified in the circular letter as a guide for judges to decide on a choice of criminal acts of murder while murder cases really need to be resolved with justice collaborators, maqasid sharia hifzul nafs (protecting lives) is a state commitment and Islam forbids killing.